On the Question of the Molecular and Genetic Mechanisms by which Bone Tissue Osteoblasts Interact with Biological Materials During Osteoplasty - Medvedeva, T.N.; Rossinskaya, V.V.; Kulagina, L.N.; Volova, L.T. (Biomedical Chemistry: Research and Methods, 2025)
The article herein sets out to show the molecular and genetic mechanisms underpinning regenerative processes in bone tissue during the implantation of biological materials. The adhesion of osteoblasts to biological materials is a pivotal step in the transfer of physicochemical signals from biomaterials to osteoblasts. Initially, bone tissue cells interact with the biological material indirectly, through specific extracellular matrix proteins, especially vitronectin, fibronectin, and type I collagen. During the period preceding direct contact of osteoblasts with the implant, it is possible for blood proteins to be absorbed on the surface of the biological material in few seconds. Exactly the formation of a "protein layer" on the implants has been demonstrated to favour the adhesion of osteoblasts. The process of adhesion of osteoblasts to blood proteins is facilitated by a specific sequence, RGD, a tripeptide consisting of the amino acids Arg, Gly and Asp. This sequence is characteristic of vitronectin, fibronectin, type I collagen, osteopontin, bone sialoprotein and thrombospondin. Integrin-related signalling pathways can be categorised into two distinct types: those that are contingent on the Src-FAK complex and those that are not. It has been established that the phosphorylation of FAK at various sites can trigger multiple signalling pathways, including the PI3K/Akt/mTOR pathway, the Ras/MAPK/ERK1/2 pathway, and the p130Cas-RhoA GTPase pathway. For signalling pathways whose action is not contingent on the Src-FAK complex, integrin-linked kinase (ILK) is a pivotal regulatory factor. Among other significant cell membrane proteins, cadherins have been demonstrated to function as signal transduction molecules, contributing to the regulation of critical cellular activities. Consequently, in addition to the physical attachment of osteoblasts to biomaterials, cell adhesion leads to the activation of several signalling pathways, among which integrin- and cadherin-related signalling pathways are the most significant.